Asymptotic uniform moduli and Kottman constant of Orlicz sequence spaces - Delpech, Sylvain (Revista Matemática Complutense, 2009)
We give lower and upp er b ounds, involving moduli of asymptotic uniform con vexity and smoothness, for the Kottman separation constant of Orlicz sequence spaces equipp ed with the Luxemburg norm.